Dosimetric scorecards express precise clinical intent: alternate hippocampal-sparing whole-brain RapidPlan models favoring target coverage and homogeneity at 30 and 20 Gy - Rayn, Kareem; Magliari, Anthony; Clark, Ryan; Rosa, Lesley; Doucet, Robert; Comeau, Line; Nichol, Alan; Ruo, Russell; Roberge, David (Frontiers in Oncology, 2024)
IntroductionThis study develops two new multi-institutional hippocampal-sparing whole-brain RapidPlan™ models (HLS-EC-WB and HMS-EC-WB) inspired by CCTG-CE.7 featuring enhanced target coverage with varying hippocampal sparing (limited and moderate).MethodsNew dosimetric scorecards were created to quantify the models’ clinical intent. The models were trained using a multi-institution dataset, and a recursive method was employed to generate consistent, high-quality plans. The models were validated using a five-case set and compared at 20- and 30-Gy prescriptions.ResultsEach model scored highest on its associated dosimetric scorecard. The new models achieved higher brain PTV prescription coverage (98%–99%) compared to the previous HSWBv2 model (95.12%), with some trade-off in hippocampal sparing.ConclusionsThree high-quality automated RapidPlan™ models for hippocampal-sparing whole brain are now available, each with a distinct dosimetric scorecard. The new models prioritize increased PTV coverage at some expense to hippocampal sparing. All models, example plans, scorecards, and scoring tools are freely available online.